Pemanfaatan Perkarangan Berbasis Hidroponik Meningkatkan Kesejahteraan Masyarakat Desa Sumber Rahayu, Kecamatan Rambang, Muara Enim: Utilization of Hydroponic-Based Yards to Improve the Welfare of the Community of Sumber Rahayu Village, Rambang District, Muara Enim - Triana, Arjuna Neni; Puspitahati, Puspitahati; Rejo, Amin; Prima, Fidel Harmanda; Saleh, Edward; Hersyamsi, Hersyamsi; Iskandar, K.H.; Panggabean, Tamaria (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service activity aims to enhance the gardening skills of residents in Sumber Rahayu Village, Rambang District, Muaraenim Regency, by teaching them to grow vegetables in their yards using hydroponic technology. This activity includes socialization, counseling, training, and coaching on hydroponic technology. The results of the activity demonstrate that hydroponic technology is effective in enhancing the community's ability to grow vegetables, with high levels of participant satisfaction (88% for satisfaction, 90% for interest, and 80% for meeting expectations). This activity opens up opportunities for the community to strive for independent food sources and increase food security, and the positive impact of this activity is evident in its sustainability.